PENGARUH PROFITABILITAS, KEPEMILIKAN MANAJERIAL, DAN GROWTH OPPORTUNITY TERHADAP KINERJA PERUSAHAAN - Ayunda Wulansari, (2022)
This research is a quantitative study that aims to determine the effect of profitability, managerial ownership, and growth opportunity on firm performance. This research uses data from the annual reports of transportation and non-building construction companies listed on the Indonesia Stock Exchange in the 2018-2020 period. This research used a purposive sampling method with the acquisition of a sampling of 15 samples. The technique used to analyze the data in this research is multiple linear regression with software STATA. Based on the results of data analysis, it can be concluded that (1) profitability has a significant positive effect on firm performance, (2) managerial ownership has no effect on firm performance, and (3) growth opportunity has no influence on firm performance. Keywords: profitability, managerial ownership, growth opportunity, and firm performance.